ASSESSMENT OF THE INCIDENCE AND CONTRIBUTING FACTORS OF POST CAESAREAN SECTION WOUND SEPSIS AMONG POSTNATAL MOTHERS AT KENYATTA NATIONAL HOSPITAL, POSTNATAL WARD - Chelimo, Agneta; Arodi, Dr. Washington; Makworo, Dr.Drusilla; Mugo, Dr.Judy (Journal of Health, Medicine and Nursing, 2018)
Purpose: The purpose of this study was to assess of the incidence and contributing factors of post caesarean section wound sepsis among postnatal mothers at Kenyatta National Hospital, postnatal ward Methodology: This was a cross sectional descriptive survey. Systematic sampling method was used to pick 212 postnatal mothers to participate in the study whereby they were picked until full saturation was achieved. Simple random sampling method was used to select the health care workers study subjects. One hundred [100] computer generated numbers were used to pick only seventy nine [79] Health care workers. Data was then analyzed through descriptive statistics using the Statistical Package for Social Science (SPSS version 20.0).Chi-square test was used to test associations between selected independent and dependent variables. Results: The study found out making 3 antenatal visits made before coming for caesarian section was significantly associated with minimal chance of sepsis OR 0.2 [95% CI 0.1-0.8], P value 0.021.Also there was no significant association between the sepsis and frequency of washing before touching your wound dressing, finishing, and dose of antibiotics prescribed and whether women of reproductive age group should be encouraged to have a well balance diet and take adequate exercise. Unique contribution to theory, practice and policy: Health education on post caesarean section wound sepsis needs to be provided to mothers during antenatal clinic. More needs to be done to encourage mothers during post Natal period to attend antenatal clinic at Kenyatta National Hospital so that prior diagnosis and teaching of mothers who have cephalopelvic disproportion(CPD) would be done and elective surgery be planned earlier. Healthcare workers should undergo sensitization on infection prevention and control.